2020
DOI: 10.3390/molecules25102320
|View full text |Cite
|
Sign up to set email alerts
|

Finding Value in Wastewaters from the Cork Industry: Carbon Dots Synthesis and Fluorescence for Hemeprotein Detection

Abstract: Valorisation of industrial low-value waste residues was preconized. Hence, carbon dots (C-dots) were synthesized from wastewaters of the cork industry—an abundant and affordable, but environmentally-problematic industrial effluent. The carbon nanomaterials were structurally and morphologically characterised, and their photophysical properties were analysed by an ensemble of spectroscopy techniques. Afterwards, they were successfully applied as highly-sensitive fluorescence probes for the direct detection of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In all cases, the emission maximum is maintained at 426 nm ( Figure S12b ). A great PL stability is observed for WP-CDs-5 between pH 1 and ~8, a characteristic that is shared with the CDs obtained from the wastewaters of olive mills [ 26 ] and cork factories [ 27 ]. Upon increasing the pH above this value, the fluorescence drops abruptly, reaching only 45% of the pristine emission at pH 11.6 ( Figure S12c PL intensity in most reported CDs is highly sensitive to pH changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, the emission maximum is maintained at 426 nm ( Figure S12b ). A great PL stability is observed for WP-CDs-5 between pH 1 and ~8, a characteristic that is shared with the CDs obtained from the wastewaters of olive mills [ 26 ] and cork factories [ 27 ]. Upon increasing the pH above this value, the fluorescence drops abruptly, reaching only 45% of the pristine emission at pH 11.6 ( Figure S12c PL intensity in most reported CDs is highly sensitive to pH changes.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of CDs from several biomass wastes has been accomplished in the last few years [ 17 , 18 , 19 , 20 ]. Examples include the use of wastepaper [ 21 ], wheat straw [ 22 ], food waste [ 23 ], tobacco leaves [ 24 ], rice residues [ 25 ], and wastewaters from olive mills [ 26 ] and the cork industry [ 27 ]. Besides our own investigations [ 26 ], research focused on olive mill wastes for preparing CDs is scarce but has been pursued by other groups.…”
Section: Introductionmentioning
confidence: 99%
“…When we measured the average fluorescence lifetime of F-NCDs, the calculated average (amplitude-weighted) lifetime was reduced from 10.2 ns to 7.68 ns with the addition of AA, suggesting that the presence of AA reduced the average lifetime of F-NCDs significantly (Figure 13b). Above all, these findings revealed that the fluorescence quenching mechanism of F-NCDs/AA system was dynamic [30,41,42]…”
Section: Mechanism For Ascorbic Acid (Aa) Detectionmentioning
confidence: 76%
“…Carbon-based nanomaterials, particularly carbon dots (C-dots) have attracted the researchers interest due their excellent luminescence, photostability and biocompatibility, encouraging their use in several fields such as biomedicine, sensing, (photo)catalysis and optoelectronics [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…C-dots can be prepared by a variety of methods (top-down and bottom-up approaches), using a great diversity of carbon sources [2]. Use of several types of wastes, either from industrial or forest origin, for C-dots production has been achieved [3,4,[6][7][8]. Coffee is one of the most consumed brews all over the world, generating large amounts of waste.…”
Section: Introductionmentioning
confidence: 99%